2011
DOI: 10.1111/j.1530-0277.2011.01456.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Myostatin Activity and Decreased Myocyte Proliferation in Chronic Alcoholic Cardiomyopathy

Abstract: Alcohol produces cardiac myocyte loss through apoptosis but also partially inhibits myocyte proliferation through myostatin up-regulation. The final result may suppose an imbalance in myocyte homeostasis, with a net loss in total ventricular myocyte mass and progressive ventricular dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 53 publications
5
19
0
Order By: Relevance
“…In a recent study by our group, we observed a non-significant downward trend of IGF-1 myocardial expression in AHT in human cardiac organ donors. Similarly, we have previously described the regulatory role of myostatin and IGF-1 in alcoholic CMP [13]. For the purpose of this study, myocardial samples were prospectively obtained from human heart donors and the effect of AHT on myostatin and IGF-1 myocardial expression was evaluated by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent study by our group, we observed a non-significant downward trend of IGF-1 myocardial expression in AHT in human cardiac organ donors. Similarly, we have previously described the regulatory role of myostatin and IGF-1 in alcoholic CMP [13]. For the purpose of this study, myocardial samples were prospectively obtained from human heart donors and the effect of AHT on myostatin and IGF-1 myocardial expression was evaluated by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…Some of these patients had been included in previous studies on heart antioxidant status [31], cardiac apoptosis [32] and myostatin myocardial expression [13].…”
Section: Selection Of Patients and Controlsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is mediated by interference with myokines (FGF-21) and local hormones and growth-factors such as myostatin [33], IGF-1 [34], ghrelin [35] and leptin [36]. Thus, ethanol decreases the myocyte proliferation rate probably by myostatin up-regulation [33] and modifies the mechanisms of cardiac plasticity [37].…”
Section: Pathogenic Factorsmentioning
confidence: 99%
“…This is mediated by interference with myokines (FGF-21) and local hormones and growth-factors such as myostatin [33], IGF-1 [34], ghrelin [35] and leptin [36]. Thus, ethanol decreases the myocyte proliferation rate probably by myostatin up-regulation [33] and modifies the mechanisms of cardiac plasticity [37]. The final balance of alcoholinduced heart effects is a clear increase in the damaging factors and a decrease in protective heart mechanisms leading to progressive cardiac myocyte damage and loss by apoptosis and necrosis and the substitution of these cells by non-functional fibrosis [38,39].…”
Section: Pathogenic Factorsmentioning
confidence: 99%